Systemic methodology applied to design (AACINI - International Journal of Industrial Engineering, 2023)
This work aims to generate a systemic methodology applied to design that considers organized connective ties of multiple variables involved in the design, which order and provide feedback, to take corrective actions based on interrelationships of parts that are not visualized in a primary way. It proposes the linking of variables through interaction nodes, with an order of relevance and impact on their systems and subsystems, with critical nodes that visualize the need for corrective actions that generate change variables that feed back into the process, originating new bonds of weighting, association and interaction of variables with a systemic approach. Its application is a tool that facilitates the design process that optimizes it and allows its parts to be adapted based on the pre-established conditions in the expected behavior of the design object, generating orderly documentation of its stages and adaptations.
Keywords: design; critical nodes; systemic